OP0215 Baseline ASDAS and CRP Predicts Future Cardiovascular Risk in Ankylosing Spondylitis: Results After 5-Year Follow-Up. (23rd January 2014) - Berg, I. J.; Semb, A. G.; van der Heijde, D.; Dagfinrud, H.; Kvien, T. K.; Provan, S. A.
Abstract : Background: Patients with ankylosing spondylitis (AS) have increased risk of cardiovascular disease (CVD), and we have previously shown in a cross-sectional study that high ASDAS is associated with atherosclerotic CVD. Objectives: To investigate whether baseline AS disease activity predicts future increased arterial stiffness. Methods: A 5-year follow-up study of hospital recruited AS patients diagnosed according to the mNY criteria, with examinations in 2003 and 2008-2009. Information on demographics, co-morbidities and medication was assessed from questionnaires. Baseline AS disease activity was assessed from questionnaires, clinical examination and blood samples (ASDAS-CRP, BASDAI, ESR and CRP). Arterial stiffness, measured as Augmentation index (AIx), was recorded in 2008-2009 (Sphygmocor apparatus, At Cor). Statistical analyses were performed in SPSS 20 using bivariate test as appropriate. Associations between disease activity and AIx (dependent variable) were analyzed in separate linear regression models, adjusted for age and gender using quartiles of baseline CRP, ESR and BASDAI. ASDAS was grouped according to the generally agreed cut-offs for ASDAS: inactive disease (<1.3), moderate (1.3-2.0), high (2.1-3.5) and very high (>3.5) disease activity. Possible confounders recorded in 2003 (smoking, BMI, level of education, use of NSAID, DMARD and TNF-inhibitors) and variables from the follow-up examination known to have a possible effect on AIx (smoking, BMI, central mean arterial pressure) were added to the model consecutively. Results: 103 AS patients participated. Baseline mean (SD) age was 48.4 (12.6) years. 56 % were male, 25% smokers, 83% used NSAIDS, 17% used DMARDs, 2% used TNF-inhibitors. Mean (SD) ASDAS was 2.5 (1.2); BASDAI 4.1 (2.3). Median (IQR) ESR was (mm/h) 13 (6-24); CRP (mg/l) 4 (2-14). In linear regression models, adjusted for age and gender, higher CRP and ASDAS were significantly associated with higher AIx while ESR was borderline significant (figure). There were no associations between BASDAI and AIx. Adjustments for confounders did not alter results. Image/graph: Conclusions: Elevated disease activity measured by CRP and ASDAS, but not BASDAI, predicted higher future AIx, indicating that inflammation and disease activity are risk factors of CVD in AS. Reducing disease activity may be a viable way of reducing excess CVD in AS. Disclosure of Interest: None Declared